GENDER DALAM PERSPEKTIF ISLAM: STUDI KEPEMIMPINAN PADA LEMBAGA EKSEKUTIF DAN LEGISLATIF DI SULAWESI TENGAH - Wahab, Gusnarib (State Institute of Islamic Studies (IAIN) Palu, 2008)
This paper deals with gender women’s leadership in the executive and legislative boards in Central Sulawesi from the perspective of Islam. The method of data collection includes documentation, observation and depth interview. The Data collected were analyzed by employing a qualitative method. The results of the research shows that (1) Islam gives the same role to women to get involved in public life as men; (2) Women’s representativeness in the executive and legislative boards (governor office) in Central Sulawesi can be said to be relatively low.Kata Kunci: gender perspektif Islam, kepemimpinan perempuan, Lembaga Eksekutif, Lembaga Legislatif